Gathering of data relevant for PV investment decisions: (WWZ Forum projects FV-71 & FV-79) - Fintan Oeri (University of Basel, Center of Business and Economics (WWZ), 2022)
This document introduces synthesised data on solar PV investments in Switzerland and an accompanying R shiny app . The data were collected as part of two WWZ Forum research projects, FV-71 and FV-79, on prices associated with green buildings. In addition to unified data on solar PV subsidies by municipality, the datasets include processed data on PV installations, PV installation potential, electricity prices, feed-in-tariffs, and population size of each geographic unit. Furthermore, linking relevant variables by geographical unit poses a substantial challenge to any analysis on the PV distribution in Switzerland. The issue primarily stems from distinct, and sometimes arbitrary, observational units (political municipalities, addresses, post codes, operators with unclear areas of activity) used in original data sources. The present document, together with an accompanying R script, provides a pragmatic approach to overcome this issue.
Keywords: 330